2016
DOI: 10.1007/s11012-016-0524-x
|View full text |Cite
|
Sign up to set email alerts
|

The PELskin project-part V: towards the control of the flow around aerofoils at high angle of attack using a self-activated deployable flap

Abstract: During the flight of birds, it is often possible to notice that some of the primaries and covert feathers on the upper side of the wing pop-up under critical flight conditions, such as the landing approach or when stalking their prey (see Fig. 1) . It is often conjectured that the feathers pop up plays an aerodynamic role by limiting the spread of flow separation . A combined experimental and numerical study was conducted to shed some light on the physical mechanism determining the feathers self actuation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…Kunze and Brücker (2012) saw that the presence of the flexible elements allowed the shedding frequency to be locked in with the most dominant eigen-frequency of the flaplets. This hints to a similar lock-in effect of the shear layer roll-up observed for the aerofoils, Rosti et al (2017). Consequently the flow-structure in the wake is changed and a reduced wake deficit is observed.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Kunze and Brücker (2012) saw that the presence of the flexible elements allowed the shedding frequency to be locked in with the most dominant eigen-frequency of the flaplets. This hints to a similar lock-in effect of the shear layer roll-up observed for the aerofoils, Rosti et al (2017). Consequently the flow-structure in the wake is changed and a reduced wake deficit is observed.…”
supporting
confidence: 66%
“…Such that they start to oscillate in the flow. This conclusion is based upon a similar observation of flow stabilisation with flaplets attached to the aft part of an aerofoil and a bluff body (Brücker and Weidner, 2014;Rosti et al, 2017;Kunze and Brücker, 2012), where the flaps act as 'pacemaker' and alter the shedding cycle, leading to a reduction in drag and lift fluctuations. It is worth to note that the herein observed stabilisation goes together with a slight reduction in the thickness of the local boundary layer edge (δ ).…”
Section: Flow Fieldmentioning
confidence: 87%
See 1 more Smart Citation
“…2008 ). Operating at high angles of attack at their characteristic Strouhal numbers allows owls to fly more slowly while still being able to generate lift ( Rosti et al. 2017 ) through the formation of LEV ( Anderson 1973 ).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental and computational studies on the wings with additional flap inspired by covert feathers have shown that passively pop-up flap enhances the lift force and improve efficiency. The studies shown above have been performed mainly under the assumption of uniform flow (Kernstine et al, 2008;Schlüter, 2009;Rosti et al, 2017). Drones are, however, expected to operate at the atmospheric boundary layer where the various unsteady wind is generated due to the friction of the wind and the ground (Watkins et al, 2006).…”
Section: Introductionmentioning
confidence: 99%